Bacteraemia following orotracheal intubation and oesophageal balloon dilatation. Issue 8 (August 1989) - Hansen, C P; Westh, H; Brok, K E; Jensen, R; Bertelsen, S
Abstract : Asymptomatic bacteraemia following balloon dilatation was assessed in 20 adults with oesophageal stricture. Asymptomatic bacteraemia occurred in 12 of 19 patients. The source of the bacteraemia appeared to be the patients' oropharyngeal flora. The bacteraemia was not of clinical importance in our patients, but might lead to endocarditis in predisposed individuals.